Petani Kelapa : Studi Antropologi Tentang Pengelolaan Kelapa di Desa Laeya Kecamatan Wakorumba Utara Kabupaten Buton Utara - Tantri, Kaliana; Zainal, Zainal; Suyuti, Nasruddin (JURNAL KABANTI: Kerabat Antropologi, 2025)
This research is entitled “Coconut Farmers: An Antropological Study  of Coconut Management in Laeya Village, North Buton. Wakorumba District, North Buton. The aim of this research is to find out how coconuts are managed in Laeya Village and what the coconut buying and selling system is in Laeya Village. This research uses Carol Steack’s theory regarding social organizations. The data collection techniques in this research were abservation and in-depth interviews. Furthermore, the data obtained was analyzed using a qualitative descriptive method. The result of this research showed that several coconut farmers in Laeya Villagege processed their own coconut farmers in Laeya Village processed their own coconuts into copra and the remaining shell will be processed into charcoal buyers. Apart from that, there are also some coconut farmers who do not process their coconuts unless they choose to sell the fruit to coconut buyers themselves in Laeya Village who implement the system. The sale and purchase of coconuts is carried out by several female farmers and also male farmers. Coconut farmers in Laeya Village first take a deposit to meet their family’s needs and the give their coconuts at harvest time to the buyer they owe money to. Those who process their coconuts into copra will sell to copra buyers and then farmers who sell the fruit will sell the coconut fruit to buyers who want to make copra.